Natal and neonatal teeth myths in a rural Nigerian community (2020)
The presence of natal/neonatal teeth in infants is sometimes associated with negative societal attitudes. Literature regarding attitudes and beliefs of residents of Igbo Ora, Nigeria, regarding natal teeth is non-existent. It is therefore important to obtain baseline data to highlight knowledge gaps regarding natal/ neonatal teeth in infants. To determine the attitudes and beliefs of residents of Igbo Ora to natal/neonatal teeth in infants. A cross sectional study was conducted among 339 women attending dental outreach programmes in Igbo Ora using a pretested 17-item semi structured questionnaire. Over two fifths (48.7%) believed that a natal tooth is seen in an evil child. A third (36.0%) mentioned that the affected child is an embarrassment to the family. Over half (61.9%) were of the opinion that a natal tooth can affect a child negatively. Of these, 104 (49.5%) and 58 (27.6%) stated that the child “would suffer stigmatization” and “engage in strange things” respectively. Mothers of children with natal teeth were usually advised to extract the teeth, 74 (21.8%), hide the child, 74 (21.8%) and perform sacrifices to appease the gods, 69 (20.4%). The belief that a natal tooth is not associated with spiritual consequences increased with higher educational qualification (p < 0.001). This study reveals that knowledge gaps regarding natal/neonatal teeth are present among inhabitants of Igbo Ora. Appropriate health education is needed for the community members particularly targeted at women and the less educated